Computerised cognitive behaviour therapy (cCBT) as treatment for depression in primary care (REEACT trial): large scale pragmatic randomised controlled trial. (11th November 2015) - Gilbody, Simon; Littlewood, Elizabeth; Hewitt, Catherine; Brierley, Gwen; Tharmanathan, Puvan; Araya, Ricardo; Barkham, Michael; Bower, Peter; Cooper, Cindy; Gask, Linda; Kessler, David; Lester, Helen; et al.
Abstract : Study question How effective is supported computerised cognitive behaviour therapy (cCBT) as an adjunct to usual primary care for adults with depression? Methods This was a pragmatic, multicentre, three arm, parallel randomised controlled trial with simple randomisation. Treatment allocation was not blinded. Participants were adults with symptoms of depression (score ≥10 on nine item patient health questionnaire, PHQ-9) who were randomised to receive a commercially produced cCBT programme ("Beating the Blues") or a free to use cCBT programme (MoodGYM) in addition to usual GP care. Participants were supported and encouraged to complete the programme via weekly telephone calls. Control participants were offered usual GP care, with no constraints on the range of treatments that could be accessed. The primary outcome was severity of depression assessed with the PHQ-9 at four months. Secondary outcomes included health related quality of life (measured by SF-36) and psychological wellbeing (measured by CORE-OM) at four, 12, and 24 months and depression at 12 and 24 months. Study answer and limitations Participants offered commercial or free to use cCBT experienced no additional improvement in depression compared with usual GP care at four months (odds ratio 1.19 (95% confidence interval 0.75 to 1.88) for Beating the Blues v usual GP care; 0.98 (0.62 to 1.56) for MoodGYM v usual GP care). There was no evidence of an overall difference between either programme compared with usual GP care (0.99 (0.57 to 1.70) and 0.68 (0.42 to 1.10), respectively) at any time point. Commercially provided cCBT conferred no additional benefit over free to use cCBT or usual GP care at any follow-up point. Uptake and use of cCBT was low, despite regular telephone support. Nearly a quarter of participants (24%) had dropped out by four months. The study did not have enough power to detect small differences so these cannot be ruled out. Findings cannot be generalised to cCBT offered with a much higher level of guidance and support. What this study adds Supported cCBT does not substantially improve depression outcomes compared with usual GP care alone. In this study, neither a commercially available nor free to use computerised CBT intervention was superior to usual GP care. Funding, competing interests, data sharing Commissioned and funded by the UK National Institute for Health Research (NIHR) Health Technology Assessment (HTA) programme (project No 06/43/05). The authors have no competing interests. Requests for patient level data will be considered by the REEACT trial management group Trial registration Current Controlled Trials ISRCTN91947481 .